PENERAPAN KONSEP GREEN MANUFACTURING PADA BOTOL MINUMAN KEMASAN PLASTIK - Wisma Soedarmadji; Surachman Surachman; Eko Siswanto (Journal of Engineering and Management in Industrial System, 2015)
Abstract Green Manufacturing is a production process that uses input with a relatively low environmental impact and produce little or no waste or pollution. Application of green manufacturing in the production process of plastic packaging beverage bottles through several stages of the coloring process, preparation of cleaning, repair environmentally friendly, and environmentally friendly conditions. Delivery bottle plastic packaging to the manufacturer for recycling reaches ± 2-3 tons in one shipping every week. Delivery is done three times a month, so that averaged reach 8-12 tons per month for waste bottles of all brands. The purpose of this research are: 1) Knowing the positive influence between staining with cleansing preparation, 2) Knowing the positive influence between the preparation of cleaning with environmentally friendly improvements, 3) Knowing the positive effect between environmentally friendly improvements to the condition of eco-friendly, 4) Knowing the positive influence between staining with environmentally friendly conditions. This study used a survey method using data analysis Partial Least Square (PLS). Results of this research are: 1) Variable staining and no significant positive effect on the variable cleansing preparation 2) Variable cleaning preparations positive and significant impact on the improvement of environment-friendly 3) Variable environmentally friendly improvements and significant positive effect on the condition of environment-friendly. 4) Variable staining and no significant positive effect on the condition of environment-friendly.